Pengaruh Kompetensi Individu, Disiplin Dan Dukungan Manajemen Terhadap Kinerja Karyawan Hotel Pelangi Kota Kupang Dengan Motivasi Kerja Sebagai Variabel Mediasi - Mooy, Dikky (Bisman - Jurnal Bisnis & Manajemen, 2022)
The performance of each person also depends on management support in the form of organizing, provision of work facilities and infrastructure, security of the work environment and working conditions. Employee performance can improve work quality, both in quality and quantity, provide new knowledge, which will help employees in solving complex problems, through a limited set of activities, and regularly, according to the responsibilities given by the organization. The research entitled “The Influence Of Individual Competency, Discipline and Management Support On The Performance Of Pelangi Hotel Employees in Kupang With Work Motivation As Intervening Variable. The problem in this research is whether individual competence, management discipline and support partially have a significant effect on employee performance with work motivation variables as mediating variables, and whether work motivation has a significant effect on employee performance.Population and Sample in this study were 34 employees. Data acquisition tools use questionnaires and direct interviews. Data analysis techniques used in this research are descriptive analysis and Partial Least Square analysis.The results of this study, management and company owners need to to increase work motivation and performance of Pelangi hotel employees andneed to pay attention to the variables that most influence.